SAT0258 Low Risk of Hepatitis B Virus Surface Antigen Seroreversion in Hbsag Negative, Anti-Hbc Positive Carriers Undergoing Rituximab for Rheumatoid Arthritis. (10th June 2014) - Varisco, V.; Viganò, M.; Batticciotto, A.; Lampertico, P.; Marchesoni, A.; Gibertini, P.; Pellerito, R.; Rovera, G.; Caporali, R.; Todoerti, M.; Covelli, M.; Notarnicola, A.; et al.
Abstract : Background: Rituximab (RTX), an anti-CD20 monoclonal antibody, is an effective treatment for Rheumatoid arthritis (RA), targeting B cells. However, the safety of this drug in hepatitis B surface antigen (HBsAg) negative/anti-hepatitis B core antigen (anti-HBc) positive carriers is still unknown. The purpose of our study is to evaluate the risk of HBsAg seroreversion in this kind of patients. Objectives: The purpose of our study is to evaluate the risk of HBsAg seroreversion in this kind of patients. Methods: We retrospectively reviewed 310 RA patients treated in 5 italian outpatient rheumatologic Clinics with RTX from August 2006 to December 2011. 35 (11, 2%) were HBsAg negative/anti-HBc positive patients and they did not undergo antiviral prophylaxis. Complete serological panel for HBV status before starting RTX infusions and adequate post-treatment follow-up were available. All patients (75% female, median age 60 years, median disease duration 8 yrs, 100% serum HBV DNA negative by sensitive PCR assay, 87% anti-HBs positive) has been treated with one or more disease-modifying anti-rheumatic drugs (83% MTX, 26% CYS, 80% PDN, 8% LEF, 6% AZA) and were eligible for RTX therapy according to international guidelines. The median period of RTX administration was 3 cycles (range: 1-8) and the therapy was ongoing at the end of observational period in 76% of cases. All patients were laboratory and clinically evaluated every three months. Serum HBsAg and serum HBV DNA were assessed in all patients every 6 months or in case of alanine aminotransferase (ALT) elevation and at the end of the follow-up period. Results: The median follow-up time was 45 months (range: 12-80). In this period 27% of patients had anti-HBs titer decrease (2 patient with a complete lost of anti-HBs levels). Only one patient (3%) had an increase of serum HBV DNA (from undetectable to 24 and 44 IU/mL, 1 week apart) without either HBsAg seroreversion or ALT increase. This virological breakthrough occurred 5 months after the first cycle of RTX and required Lamivudine treatment which successfully suppressed viral replication in 4 weeks. One patient (3%) had an ALT flare, not related to HBV reactivation. Conclusions: The retrospective review of our multicentre experience suggest that an adequate monitoring of HBsAg and HBV DNA levels in RA patients HBsAg negative/anti-HBc positive, as recommended by international guidelines, allows us to avoid the antiviral prophylaxis during RTX treatment. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2656